Turbidity Changes in the Tigris River Using Satellite Data During the COVID-19 Related Lockdown - H. Obaid , Omar; abdulAmeer, inbethaq (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
In the present study, an attempt has been made to study the change in water quality of the river in terms of turbidity during lockdown associated with COVID-19. Iraq announced the longest-ever lockdown on 25 March 2020 due to COVID-19 pandemic. In the absence of ground observations, remote sensing data was adopted, especially during this period. The change in the visible region's spectral reflectance of water in part of the river has been analyzed using the Landsat 8 OLI multispectral remote sensing data at Tigris River, Salah al-Din province (Bayji / near the refinery), Iraq. It was found that the green and red bands are most sensitive and can be used to estimate turbidity. Furthermore, the temporal variation in turbidity was also analyzed through a normalized difference turbidity index NDTI at each location. The NDTI decreased by 7.14% in April 2020 (lockdown period) as compared to November 2020 (6 months after lockdown), when it was observed that the turbidity in the river (near Bayji oil refinery) had drastically decreased. The study confirmed that the remote sensing approach can be used to make qualitative estimates on turbidity, even in the absence of field observations. It was concluded that the water quality of Tigris River has improved and has shown signs of restoration.